Interpretasi Esoteris Jihad dalam Tafsīr Ibn 'Arabi (Ta'wīlāt al-Kasyani) - Darmawan Darmawan (Qur'an and Hadith Academic Society, 2020)
Reading the Qur'an which is limited to outward level is basically contrary to Islamic scientific traditions which give great attention to the inner aspects. As a result, the breadth of key concepts of Qur’anic teachings, including the teachings of jihad, became narrow and dry. That will trigger the issue of religious social pathology in the form of tolerance crisis, radicalism even terrorism. So an effort is needed to bring back Sufi interpretation of the verses of jihad that focuses on the inner dimension and not negate the outward dimension. The method used in this research is maudhu'i and descriptive-analytical interpretation. This study finds that jihad is an effort to encourage the soul to endure bodily difficulties and to oppose lust in everything that aims to pick up self-perfection. In Tafsīr Ibn 'Arabi, there are three meanings of jihad esoterically; First, jihad is an attempt to eliminate the reprehensible traits which brings up a concept of jihad: “the key to the success of jihād fī sabīlillah which is fanā bi kulliyāt or total self-annihilation”. Second, jihad is an effort towards maqām of human spiritual perfection which brings up a rule of jihad: “the higher or the more perfect a person is, the greater his jihad”. Third, jihad is an attempt to sacrifice wealth, body and soul. This sacrifice is a result of fulfillment of the above principles of jihad